GreenSDN: energy efficiency in software defined networks. - Rodrigues, Bruno Bastos (2016)
A significant number of protocols and capabilities have been proposed in recent years in response to the demand for reducing the amount of energy consumed by the network infrastructure. Besides rising economic issues, there is a widespread sensitivity to ecological impacts since both energy costs and electrical demands are in a upward trend. In this scenario, the development and validation of energy saving strategies are a key point of making networks more efficient. However, there is a lack of experimental environments designed specifically to emulate and to validate such energy efficiency solutions. This work proposes an environment not only supporting the development and discussion of energy-saving solutions but also management applications considering energy-saving primitives. For this purpose, the environment is built considering the implementation of energy efficiency capabilities that are representative of each network scope (interface, device, and network) in the Mininet environment taking as a basis the Software-defined Networking (SDN) paradigm. The environment proposed was evaluated with different experiments by comparing the energy savings obtained by activating these energy-efficiency capabilities.